Managing image: The self-praise of celebrities on social media. (December 2020) - Guo, Yaping; Ren, Wei
Highlights: This study investigates the self-praise of Chinese celebrities on microblogs. The results found three main categories of self-praise strategies. The Chinese celebrities tend to praise themselves implicitly or in a modified way. The factors of the celebrities' use of self-praise strategies are explicated. Implications for celebrities' image management and Chinese politeness are discussed. Abstract: Studies on self-praise have focused on ordinary people's self-praise strategies both in oral communication and on social media. However, little research has examined how celebrities perform such speech acts. This study investigates the pragmatic strategies used in the self-praise of Chinese celebrities on social media microblogs. A dataset of 300 microblogs containing self-praise was collected from 10 Chinese celebrities (5 men and 5 women) on the Chinese microblogging site Weibo. This study analyses the types of self-praise strategies and the percentage of each strategy employed by the celebrities on Weibo. The results indicated that three main categories of self-praise strategies were employed, namely, modified explicit self-praise, implicit self-praise and explicit self-praise without modification, in decreasing order of frequency. In addition, the study explicates the factors underlying Chinese celebrities' use of self-praise strategies to maintain a positive image. This study adds to the under-investigated areas of celebrities' self-praise in online contexts and celebrities' image management. Implications for politeness research in Chinese are also discussed.